Leucemia linfocítica crônica: avaliação de fatores prognósticos e sua relação com o estadiamento da doença - Tatiane Vieira Braga (2017)
Chronic Lymphocytic Leukemia (CLL), according to the World Health Organization (WHO) classification, is a B lymphocyte neoplasm. The clinical evolution is extremely variable among the individuals affected, with survival ranging from a few months to many years. Evaluating new prognostic biomarkers in CLL becomes extremely important for the early identification of individuals who have experienced rapid disease progression and who may benefit from an individualized treatment protocol. Among these biomarkers, evaluation of microRNAs, Bcl-2, ZAP-70 and Ang-2 may contribute to the prognosis of patients with CLL. In this study, 43 patients with CLL, from the Hematology and Oncology Unit of the Hospital das Clínicas of the Federal University of Minas Gerais, and 15 control subjects were evaluated. In the overall evaluation of leukocytes, lymphocytes, hemoglobin and platelets, significant differences were found when comparing the patients and the control group. Significant differences in the expression of miR-15a (p <0.001) and miR-16-1 (p <0.001) and in plasma concentration of Bcl-2 (p <0.001) were observed when comparing the patients and the control group. In Ang-2 expression, a significant difference in Ang-2 expression was observed when compared to patients and controls. In contrast, in the evaluation of ZAP-70 expression no significant difference was found. The data analyzed together suggest that the markers miR-15a and miR-16-1, in addition to Bcl-2, are associated with imbalance in the apoptosis process, which would lead to accumulation of lymphocytes and worsening of the disease.